Chronic ecotoxicology and statistical investigation of ciprofloxacin and ofloxacin to Daphnia magna under extendedly long-term exposure. (15th December 2021) - Nguyen, Tan-Duc; Itayama, Tomoaki; Ramaraj, Rameshprabu; Iwami, Norio; Shimizu, Kazuya; Dao, Thanh-Son; Pham, Thanh-Luu; Maseda, Hideaki
Abstract: Ciprofloxacin (CFX) and ofloxacin (OFX) are two of the most often used fluoroquinolone antibiotics, and their residues are found in large amounts in various aquatic settings. However, the toxicity tests of CFX using eukaryotic organisms such as Daphnia magna are inadequate, and the test result of OFX is currently unknown. Therefore, the chronic toxicity test for D. magna was performed during 42 days under exposure to CFX and OFX concentrations of 50, 500, and 5000 μg L −1 . All exposure conditions did not cause mortality for D. magna . CFX exposure at 500 μg L −1 resulted in an earlier oogenesis date and increased brood size in the second birth. The Poisson-based generalized linear mixed-effects model revealed that the reduction of fertility was statistically significant for the CFX and OFX exposures at 5000 μg L −1 . On the other hand, the production of dead eggs as offspring degradation was also found significantly as maternal D. magna exposed to antibiotics at 5000 μg L −1 . In addition, following long-term exposure to antibiotics, maternal adaptation to antibiotics was established for offspring deterioration and fertility. However, the OFX exposure showed that the fertility-suppressed effects continued for a longer period than the CFX exposure. Although no rational explanation has yet been given for the more substantial effect of OFX on reducing fertility than CFX, molecular cell biology and symbiotic microbial flora derived from previous studies could explain our ecotoxicological results. This study is the first report for the OFX chronic toxicities on D. magna by comparing it to the toxicity of CFX. Our study contributes to guiding the future impact assessment of fluoroquinolone antibiotic pollution on ecosystems, including the need for new statistical methods in ecotoxicological studies. Graphical abstract: Image 1 Highlights: New aspects of chronic CFX toxicities reported. Chronic OFX toxicities were firstly reported for D. magna . CFX and OFX exerted offspring degradations. Long-term adaptation of maternal D. magna obtained. Rigorous statistical analysis was applied for ecotoxicological data.